Transparency and access to information: An analysis of the demand for tax information in brazil's federal revenue - Grigoleto, Maira Cristina [UNESP]; Gama, Janyluce Rezende; Gama, Juliano Rezende (Universidade Federal de Santa Catarina (UFSC), 2021)
Objective: The legal provisions related to information access in Brazil materialize the obligations of public administration bodies in providing information of citizens interest, and must have effective and efficiency transparency mechanisms. In consideration of these premises, this article aims to analyze, through information access requests addressed to the Brazilian Federal Revenue Service, between 2014 and 2019, how the instruments of active transparency, available on the agency's website, may be linked to the number of information requests. Method: This is a research with a qualitative approach, characterized as exploratory in terms of objectives and, in relation to procedures, as bibliographic and documentary. Result: The results demonstrate a drop, in the last two years, in the number of information requests to the Federal Revenue Service of Brazil, either by citizens and companies, which may be related to changes in the instruments of active transparency. Conclusions: It is concluded that the improvements in the information environments, which provided 95% of the services in virtual form in 2019, and also the effort in expending mechanisms of information management and active transparency, such as: The use of satisfaction surveys, the publication of full content of tax consultation, the corporate structure and administrators in registering legal entities and data from rural properties, may have contributed to reducing the information requests to the Federal Revenue of Brazil.
TRANSPARÊNCIA E ACESSO À INFORMAÇÃO: UMA ANÁLISE DA DEMANDA POR INFORMAÇÕES FISCAIS NA RECEITA FEDERAL DO BRASIL
Keywords: Access to Information Law; Information management; Secretariat of the Federal Revenue Brazil; Transparency of Information